Recent progress in metal–organic frameworks for lithium–sulfur batteries - Zhong, Y.; Xu, X.; Liu, Y.; Wang, W.; Shao, Zongping (Pergamon, 2018)
© 2018 Elsevier Ltd The development of novel electrochemical energy storage systems has induced a great evolution of sustainable production and life. Lithium–sulfur (Li–S) batteries show a significant potential of becoming the next-generation energy storage systems, even though several vital problems, especially the dissolution and loss of active polysulfides, still hinder their practical application. Metal–organic frameworks (MOFs), a novel class of porous crystalline materials, and their derived materials, exhibit great potential for anchoring soluble polysulfides due to the unique physical and surface chemical property. In this review, we dedicate to review strategies for designing MOF-based and MOF-derived materials as hosts and functional polysulfide barriers for Li–S batteries. By revisiting three most important parameters for the design of hosts, namely conductivity, porosity and chemisorption to polysulfides, we hope to gain a greater understanding of how these MOF-related materials promote the electrochemical performance and the cycle stability of Li–S batteries. We also summarize the recent advances of two types of polysulfide barriers working based on an adsorbing-reutilization approach and a blocking approach. Finally, we point out the main challenges and some perspectives for the future development of this promising area.